High-performance liquid chromatography purification of homogenous-length RNA produced by trans cleavage with a hammerhead ribozyme. - Shields, T P (1999)
An improved method is presented for the preparation of milligram quantities of homogenous-length RNAs suitable for nuclear magnetic resonance or X-ray crystallographic structural studies. Heterogeneous-length RNA transcripts are processed with a hammerhead ribozyme to yield homogenous-length products that are then readily purified by anion exchange high-performance liquid chromatography. This procedure eliminates the need for denaturing polyacrylamide gel electrophoresis, which is the most laborious step in the standard procedure for large-scale production of RNA by in vitro transcription. The hammerhead processing of the heterogeneous-length RNA transcripts also substantially improves the overall yield and purity of the desired RNA product.